Analysis of Student Understanding Related to Indefinite Integral Concepts Through Cooperative Learning Assisted Media Interactive Animated PowerPoint Learning and Indefinite Integral Matter - Sihombing, Rizky Agassy; Muslim, Muslim; Rahman, Taufik; Rahma, Aulia Eka; Hutagalung, Jennie Febrina; Sitanggang, Winanta; Karimi, Amir (Universitas Islam Negeri Sunan Kudus, 2024)
This research aims to determine students' understanding of integral calculus. This qualitative study investigates students' responses and understanding of integral calculus, with a particular focus on indefinite integrals. The study employed cooperative learning and animated PowerPoint (PPT) media. Data were collected from 117 students across 37 educational institutions, representing various classes and majors. The study, conducted online, comprised nine questions addressing students' attitudes, perceptions, and behaviours towards learning integral calculus. The findings reveal that while a majority of students express interest in mathematics, 26.5% have a good understanding of integral calculus, 45.3% find it average, and 18.8% struggle. For indefinite integrals, 28.2% understand them well, 45.3% find them average, and 19.7% struggle. Regarding learning methodologies, 60.7% of students express a preference for learning models integrating various media over traditional teacher-centric approaches. Additionally, 59.8% find animated PPTs helpful in understanding Integral Calculus. Additionally, 51.3% prefer a combination of traditional teaching and animated PPTs. Furthermore, the study reveals a strong inclination towards group learning models over individual learning. Notably, the majority of students correctly solved the indefinite integral problems provided, indicating a satisfactory understanding of the subject matter. Students generally exhibit a positive attitude towards learning Integral Calculus, especially when utilizing cooperative learning methods and animated PPTs. These findings underscore the importance of incorporating diverse teaching strategies to enhance student engagement and comprehension in mathematics education. Penelitian ini bertujuan untuk menilai pemahaman siswa dan mahasiswa tentang kalkulus integral. Studi penelitian kualitatif ini menyelidiki respons dan pemahaman mahasiswa terhadap Kalkulus Integral, dengan fokus khusus pada topik integral tak tentu, dengan menggunakan pembelajaran kooperatif dan media PowerPoint animasi (PPT). Sebanyak 117 siswa dan mahasiswa dari 37 lembaga pendidikan di berbagai kelas dan jurusan berpartisipasi dalam penelitian ini. Data dikumpulkan melalui kuesioner online yang terdiri dari sembilan pertanyaan, yang membahas sikap, persepsi, dan perilaku mahasiswa terhadap pembelajaran Kalkulus Integral. Temuan menunjukkan bahwa sebagian besar mahasiswa (59,8%) menunjukkan minat dalam matematika. Namun, sementara 26,5% mengklaim pemahaman yang baik tentang kalkulus integral, 45,3% menganggapnya hanya biasa, dan 18,8% kesulitan memahami konsep tersebut dengan baik. Demikian pula, 28,2% memahami integral tak tentu dengan baik, sementara 45,3% menganggapnya biasa, dan 19,7% mengalami kesulitan dalam pemahaman. Mengenai metodologi pembelajaran, 60,7% mahasiswa menyatakan preferensi terhadap model pembelajaran yang mengintegrasikan berbagai media dibanding pendekatan tradisional yang berpusat pada guru. Selain itu, 59,8% menganggap PPT animasi bermanfaat dalam memahami Kalkulus Integral. Namun, 51,3% lebih memilih kombinasi pengajaran tradisional dan PPT animasi. Selain itu, penelitian ini mengungkap kecenderungan kuat terhadap model pembelajaran kelompok (70,1%) dibanding pembelajaran individual (13,7%). Secara mencolok, mayoritas mahasiswa (74,4%) berhasil menyelesaikan masalah integral tak tentu dengan benar, menunjukkan pemahaman materi yang memuaskan. Secara umum, mahasiswa menunjukkan sikap positif terhadap pembelajaran Kalkulus Integral, terutama saat menggunakan metode pembelajaran kooperatif dan PPT animasi. Temuan ini menekankan pentingnya menggabungkan beragam strategi pengajaran untuk meningkatkan keterlibatan dan pemahaman mahasiswa dalam pendidikan matematika.